Energy Efficiency Studies - Modelling and Analysis of Solar Tracker System - Bhateja, Pranshu; Gupta, Ajay (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Solar energy is of key importance to meet the increasing demands of the electrical power needs of the society as solar energy is available in abundance, is free, clean and pollution free in nature. In order to obtain more power by increasing the receptance of incident rays from sun, a solar tracking mechanism has been developed. This paper presents an energy efficiency case study of a single-axis solar tracker which converts solar energy to electrical energy. The tracker is programmed in such a way that it gets tilted to follow sun’s movement accurately throughout the day. It was observed that the generated power output with tracking is higher in comparison to the fixed PV system. How to cite this article: Bhateja P, Gupta A, Sharam VS. Energy Efficiency Studies - Modelling and Analysis of Solar Tracker System. J Adv Res Alt Energ Env Eco 2019; 6(3&4): 1-6.